Morphological and Functional Features of the Sex Steroid-Responsive Posterodorsal Medial Amygdala of Adult Rats - Rasia-Filho, A.A.; Haas, D.; de Oliveira, A.P.; de Castilhos, J.; Frey, R.; Stein, D.; Lazzari, V.M.; Back, F.; Pires, G.N.; Pavesi, E.; Winkelmann-Duarte, E.C.; Giovenardi, M. (Mini Reviews in Medicinal Chemistry, 2012)
The rat posterodorsal medial amygdala (MePD) expresses receptors for gonadal hormones and integrates sex steroid-sensitive subcortical networks. Male-female differences are found in the morphology, connectivity, and local neuropil structure of MePD. For example, dendritic spine density is sexually-dimorphic and changes with the estrous cycle and following gonadal hormones manipulations. Due to its connectivity, the MePD may affect emotionally-loaded social behaviors, according to a former Newman's seminal proposition. Unilateral fiber-sparing ibotenic acid damage of the MePD does not impair male sexual behavior. However, microinjecting glutamate and histamine into the right MePD facilitates ejaculation. Further, MePD-lesioned rats are not different from normal rats in anxiety-like behavior as evaluated by the elevated plus maze test or innate fear test induced by a live cat. In another study, an adapted model for inducing aggressive behavior in rats by a brief period of restraint prior to the resident-intruder paradigm was used to study Fosimmunoreactivity in the MePD. Following stressful stimulation (restraint) or the restraint and fight condition, but not after aggression alone, Fos-immunoreactivity was detected in the MePD. Microinjecting the inhibitory neuropeptide somatostatin into the right MePD notably reduces fighting behavior without affecting locomotion. Overall, these data indicate that sex steroids and local neurochemical stimulatory/inhibitory transmitters modulate the MePD and reinforce the idea that this area is a node for modulating social behavior neural networks.
Keywords: sexual behavior